Challenges and Opportunities in Human Resource Management Transformation in Education in the Digital Age - Dyan Paramitha Darmayanti; Darman Manda; Kurnia Ali Syarif (Universitas Negeri Makassar, 2026)
This study identifies challenges, opportunities, and solutions in human resource management in education in the digital age. We used a literature review approach to analyze literature related to the application of technology in HRM and its impact on the efficiency and transparency of teacher performance management. The results reveal that the main challenges include limitations in technological infrastructure, low digital skills among educators, gaps in technology access in remote areas, and education policies that do not fully support digitalisation. However, digitalisation offers opportunities such as increased efficiency in performance evaluation, easier access to technology-based training, and the use of data for more accurate decision-making. This study also proposes solutions to overcome these challenges, such as increasing investment in technological infrastructure, developing digital-based training, and formulating more in-depth education policies. We anticipate that the findings of this study will contribute to more effective education policies and enhance the quality of human resource management in educational institutions in the digital era.